Adsorption ability of rare earth elements on clay minerals and its practical performance - 肖燕飞 黄莉 龙志奇 冯宗玉 王良士 (Journal of rare earths, 2016)
The adsorption behaviors of rare earth elements on clay minerals would have great influence on the mineralization process and the leaching process of the ion-adsorption type rare earths ore.In this work,the adsorption thermodynamics of REEs on kaolin were investigated thoroughly and systematically.The experimental results showed that the adsorption characteristics of La,Nd,Y on kaolin did fit well with the Langmuir isotherm model and their saturated adsorption capacities were 1.731,1.587 and 0.971 mg/g,respectively.The free energy change（ΔG）values were –16.91 kJ/mol（La）,–16.05 kJ/mol（Nd）and –15.58 kJ/mol（Y）,respectively.The negative values of ΔG demonstrated that the adsorption of rare earth on kaolin was a spontaneously physisorption process.The deposit characteristic of the volcanic ion-adsorption type rare earths ore and the behavior of the rare earth in the column leaching process were also developed here.With the increase of the ore body depth,the distribution of the LREEs decreased and the HREEs increased.And the slight differences in the adsorption ability of REEs on clay minerals led to the fractionation effect in the column leaching process.These developed more evidences and better understanding of metallogenic regularity,and provided a theoretical basis and scientific approach to separation of the HREEs and LREEs in the leaching process.